Penegakan Hukum Pajak Melalui Penggunaan Sandera Pajak Dalam Penagihan Utang Pajak Di Indonesia - Yeni Nur Arifin (Universitas Pendidikan Ganesha, 2021)
Taxes make a major contribution to the source of state revenue which is used to finance development in Indonesia. However, there are still many taxpayers / tax insurer who are not compliant in paying taxes. The problems in this study are why the government uses tax hostages in collecting tax debts, how hostages are used as a means of force in collecting tax debts and how hostage-taking is viewed from a juridical aspect. The research method used in this research is normative legal research method. The result of the research is that there are several factors that become the reasons for tax hostage taking. The government (fiskus) in collecting tax debt with tax hostages has been carried out in accordance with the provisions of the law. Based on the aspect of legal certainty, tax hostages in Indonesia already have a legal umbrella, namely Law no. 9 of 2000 and several other regulations. From the aspect of justice, legal protection is provided to taxpayers / tax insurer who are subject to tax hostages. From the benefit aspect, the application of tax hostages is beneficial in increasing taxpayer compliance.